Adenocarcinoma gástrico de células em Anel de Sinete: um relato de caso - FADONI, Gabriel Augusto (2021)
Objectives: report a gastric adenocarcinoma of signet ring cells clinical case in a female patient with a previous medical history of ovarian cancer, demonstrating a diagnostic, clinical and nutritional evolution. Case description: 53-year-old woman, caucasian, goes to a medical appointment with a palpable mass complaint in periumbilical region (mesogastrium). Due to the suspicion of a cancer, she was referred to performing a magnetic resonance imaging of total abdomen, which showed an expansive large solid formation in left adnexal region, extending to the left flank and left hypochondriac region, with probable neoplastic origin. Total hysterectomy and anatomopathological examinantion were done. Immunohistochemical examination confirmed a mucinous character. The patient was followed up with an oncologist, who requested an upper endoscopy with biopsy. Another anotomopathological study was performed, evidencing proliferation of epithelioid cells with a signet-ring pattern in gastric mucosa of the antro-pylorus type. Immunohistochemical study confirmed the diagnosis of poorly differentiated adenocarcinoma with “signet-ring” cells. Conclusions: the correct investigation’s importance is undeniable in signet-ring cells adenocarcinoma cases, since its increase in incidence is evident, associated with more agressive conditions, requiring quick and effective diagnosis, as done in the case. It is essential to perform upper gastrointestinal endoscopy for gastric symptoms, being highly available for these cases. Finally, we reiterate the importance of a multidisciplinary approach with a nutritionist, enabling the best gastrointestinal function recovery.